Foldables as a resource for vocabulary teaching - Martrus Jaramillo, Israel José (2023)
The purpose of this research is to know about one of the resources to improve English vocabulary in students through the use of three-dimensional graphic organizers such as Foldables. Foldables are a good way to retain in students’ brains new words, and this is essential for students to communicate in written, and oral form. It was a bibliographic methodology because the information was found from different repositories around the world. I conclude that Foldables graphic organizers help students to remember vocabulary studied because it is a visual and kinesthetic activity and students usually enjoy having to manipulate, create material and drawing or pasting pictures. The uses of Foldables help students to develop their creativity by making different foldable forms and they have the opportunity to experiment with real situations when they use vocabulary provided with sentences, definitions and images. Furthermore, it involves students in an effective way to learn due to the fact that Foldables permit elicit students ‘previous knowledge, confirm knowledge and receive new learning.